Experimental study on the performance of oil-free twin-screw expanders for recovering energy in fuel cell systems. (25th January 2020) - Wang, Chuang; Xing, Ziwen; Sun, Shizhong; Chen, Wenqing; He, Zhilong
Highlights: Water-cooled dry oil-free twin-screw expanders are developed for fuel cell systems. A detailed contrast experiment is performed on three expanders. Effect mechanisms of operating conditions on expander performance are identified. The direction for further improvement and optimization of expanders is pointed out. Abstract: Fuel cell systems are considered to be one of the best alternative power sources for automobiles to replace internal combustion engines. For the Proton Exchange Membrane fuel cell operated at the high pressure, adding an expander downstream the stack to recover the pressure energy of air exhausted from the stack is an effective way to reduce the actual power consumption of the compressor and improve overall system efficiency. This paper aims to explore operating characteristics of the twin-screw expander under different operating conditions and geometric construction, and thus find out proper design parameters. Hence, a detailed contrast experiment is performed on three expanders to investigate the effect of the suction port area and rotor length on the expander performance. Besides, the influences of rotating speed and suction pressure on the performance of expanders including mass flowrate, filling factor and recovered power are analyzed. By analyzing the experimental results, the relevant influence mechanisms of operating conditions on the expander performance are explained according to the equations of these performance parameters. Meanwhile, the reasons why the developed twin-screw expanders have unsatisfactory performance are recognized. Finally, the directions for further improvement and optimization of the oil-free dry twin-screw expanders used in fuel cells in the future work are pointed out based on the research results.